Searching for the 17th century on Nevis : the survey and excavation of two early plantation sites - Philpott, Robert A., (Early colonial settlement and landscape of Nevis and St. Kitts ;, 2021)
A monograph dedicated to the archaeological investigation of the landscape, buildings and artefacts of the Eastern Caribbean by the Nevis Heritage Project. It presents the results of documentary research and excavation on two sugar plantation sites on the island of Nevis.